Enhancing TVET Learning: Aesthetic and Pedagogical Module Design Approach - Shen Wen; Yunus, Faizal Amin Nur; Hashim, Suhaizal (Online Journal for TVET Practitioners, 2025)
Currently, the field of education has evolved rapidly, particularly in teaching and learning methods, which now extend beyond just the concept and curriculum of education. Modules are commonly utilized in technical fields to enhance knowledge and skills in the teaching and learning process, particularly in Heating, Ventilation, and Air Conditioning (HVAC), a fundamental area in Technical and Vocational Education and Training (TVET). Incorporating aesthetics in technical learning modules enhances engagement by integrating visual, sensory, and emotional elements. This approach boosts cognitive involvement, motivation, and knowledge retention, creating a more immersive learning experience. As such, the HVAC learning module does not effectively engage cognitive processes, hindering the deep understanding and retention of crucial concepts among learners. Therefore, the main objective of this study is to design, develop and evaluate the effectiveness of the Refrigerant Handling Learning Module for Air Conditioning Systems. The module’s design followed the Sidek and Jamaluddin Model, comprising two phases and 8 steps that must be followed during the learning module’s creation process. Additionally, this module has been designed based on the Felder-Silverman learning style as a pedagogical technique. This study employs a quantitative methodology utilizing a questionnaire as the research instrument. Three experienced experts in the Refrigeration and Air Conditioning industry provided feedback on the assessment of the developed learning module. The questionnaire evaluates three main aspects: the suitability of module content, module design and module functionality. The questionnaire analysis will be displayed as a percentage. The study determined that the learning module’s development achieved its objectives and was deemed satisfactory. The researcher’s learning module intends to improve the efficacy and efficiency of teachers and students in the educational process. Ultimately, it is anticipated that the created learning module will be advantageous and yield favorable outcomes in terms of teaching and learning effectiveness for its users.